Implementation of Da’wah Training and Social Interaction between Muslim and Christian in Bandung - Aep Kusnawan (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2018)
The purpose of this study was to determine: implementation of traning dakwah about the religious motives of Muslims interacting with Christians, patterns of Muslims interaction with Christians and the influence of religious motives between Muslims and Christians and the effect on the pattern of interaction between them in Bukit Permata Housing, Cinunuk, Cileunyi District of Bandung Regency. This study uses a case method with qualitative and quantitative approach, which is believed to be capable of being used to reveal the specific situation in a community using social facts emerge. The research method chosen by the researchers is a case study. That's because the object to be studied regarding a specific phase or typical of the whole personality, and aims to obtain an adequate picture of the religious motives of Muslims interacted with Christians is the nature and distinctive character of the cases in Bukit Permata Housing Karsamanik. Research conducted involving 25 respondents with various predetermined criteria, based on the following conditions: (1). Respondents Muslims who have lived with Christian proximity, (2). Respondents are members of the Housing society Bukit Permata Karsamanik who has settled for at least 1.5 years; and (3). Respondents were considered to meet the requirements to provide a response regarding research themes; From the research conducted, the results obtained in the calculation of the indicators of the implementation Dakwah Training shows that religious motives of Muslims interacting with Christians, obtained an average value of 32.4: 14 = 2.30. If the qualifying criteria are interpreted at the high and low motives, the figures were included in the category quite well. The result of the calculation of the indicators associative patterns of social interaction between Christians Muslims with values obtained by an average of 36.3: 14 = 2.60. If the qualifying criteria are interpreted at the high and low motives, the figure is well categorized either. While the index value obtained correlation of 0.31 which is in the interval from 0.21 to 0.40 with a lower category. The hypothesis testing showed that tcount obtained is at 1.62, while the value of ttable 1.71. With these results, the hypothesis (H0) is received and the alternative hypothesis (H1) declined. Based on the calculation, the influence of variable X to Y varabel is 5%. Thus it can be said that, patterns of social interaction of Muslims with Christians influenced by religious motives with a value of 5% and 95% influenced by other factors. Religious motives of Muslims in interacting with Christians, is quite good. The pattern of interaction between Muslims with Christians, either. And the influence of religious motives to the interaction patterns among those with a value of 5%.